Distinct Immunological Profiles Help in the Maintenance of Salivary Secretory IgA Production in Mild Symptoms COVID-19 Patients - Santos, Juliana de Melo Batista dos; Amaral, Jonatas Bussador do; França, Carolina Nunes; Monteiro, Fernanda Rodrigues; Alvares-Saraiva, Anuska Marcelino; Kalil, Sandra; Durigon, Edison Luiz; Oliveira, Danielle Bruna Leal; Rodrigues, Silvia Sanches; Heller, Debora; Welter, Eliane Aparecida Rosseto; Pinho, João Renato Rebello; et al. (Frontiers in Immunology, 2022)
Background Relevant aspects regarding the SARS-CoV-2 pathogenesis and the systemic immune response to this infection have been reported. However, the mucosal immune response of the upper airways two months after SARS-CoV-2 infection in patients with mild/moderate symptoms is still not completely described. Therefore, we investigated the immune/inflammatory responses of the mucosa of the upper airways of mild/moderate symptom COVID-19 patients two months after the SARS-CoV-2 infection in comparison to a control group composed of non-COVID-19 healthy individuals. Methods A cohort of 80 volunteers (age 37.2 ± 8.2), including non-COVID-19 healthy individuals (n=24) and COVID-19 patients (n=56) who presented mild/moderate symptoms during a COVID-19 outbreak in Brazil in November and December of 2020. Saliva samples were obtained two months after the COVID-19 diagnosis to assess the levels of SIgA by ELISA and the cytokines by multiplex analysis. Results Salivary levels of SIgA were detected in 39 volunteers into the COVID-19 group and, unexpectedly, in 14 volunteers in the control group. Based on this observation, we distributed the volunteers of the control group into without SIgA or with SIgA sub-groups, and COVID-19 group into without SIgA or with SIgA sub-groups. Individuals with SIgA showed higher levels of IL-10, IL-17A, IFN-γ, IL-12p70, IL-13, and IFN-α than those without SIgA. In intergroup analysis, the COVID-19 groups showed higher salivary levels of IL-10, IL-13, IL-17A, and IFN-α than the control group. No statistical differences were verified in the salivary levels of IL-6 and IFN-β. Lower IL-12p70/IL-10 and IFN-γ/IL-10 ratios were found in the control group without SIgA than the control group with SIgA and the COVID-19 group with SIgA. Conclusion We were able to present, for the first time, that associations between distinct immunological profiles can help the mucosal immunity to maintain the salivary levels of SIgA in COVID-19 patients two months after the SARS-CoV-2 infection.